Effect of Audio and Audiovisual Distraction Technique on Anxiety of Pediatric Patients During Pit and Fissure Sealant Application: A Clinical Trial (Academia Journal of Medicine, 2024)
This clinical trial evaluates the impact of audio and  audiovisual distraction techniques on reducing anxiety in  pediatric patients undergoing pit and fissure sealant  application. A total of 60 children aged 6-12 requiring  sealant application were randomly assigned into three  groups: Control (no distraction), Audio distraction  (listening to music), and Audiovisual distraction (watching  cartoons). Anxiety levels were measured using the Venhem  Anxiety Rating Scale (VARS) before and after the  procedure. The study found a significant reduction in  anxiety levels in the audio and audiovisual distractiongroups compared to the control group. Specifically, theaudiovisual group showed the greatest reduction in VARSscores, followed by the audio group.
Keywords: Pediatric dental anxiety; Audio distraction; Audio visual distraction